(untitled) (Proceedings of the International Conference on Education, 2021)
Migratory displacements, the multiplicity of ethnic groups, and tremendous cultural diversity in today’s society (culture, sex, religion, language, education, sexual orientation) worldwide have made it necessary for health professionals to address the immediate demands and needs of society. The objective of this study was to identify the development of diversity competency through educational innovations. The methodology was quantitative, descriptive, and cross-sectional. The tool was a questionnaire used as a pre-test and post-test to measure the value perceived by the students participating in our university’s Tec Week activities. It was applied to the total number of students enrolled in the Tec Week activities. The questionnaire was answered by 21 students participating in the activities "Me, You, Others, Us" and "Diversity in a Globalized World." Focus groups validated the questionnaire; for statistical analysis, the Wilcoxon test was used and Cronbach’s Alpha (0.97). The results of the Tec Week activities "Me, You, Others, Us" and "Diversity in a Globalized World" showed the dimension in which students feel more confident in their self-reflection. For the diversity competency, it was "Strengthen my Support for Gender Equality." However, the activity in which the students did not feel confident in both the pre and post-tests was "Participate in Inclusion Initiatives with Vulnerable Groups." The development of diversity competency contributes high value to the training of health professionals. It is based on human rights and individuality and considers the patient’s characteristics, expressing openness, interest, and disposition towards the diversity surrounding them.